2007
DOI: 10.1111/j.1530-0277.2007.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatments for Patients With Dual Diagnosis: A Review

Abstract: Although no treatment was identified as efficacious for both psychiatric disorders and substance-related disorder, this review finds: (1) existing efficacious treatments for reducing psychiatric symptoms also tend to work in dual-diagnosis patients, (2) existing efficacious treatments for reducing substance use also decrease substance use in dually diagnosed patients, and (3) the efficacy of integrated treatment is still unclear. This review provides a critique of the current state of the literature, identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(61 citation statements)
references
References 97 publications
(83 reference statements)
2
56
0
3
Order By: Relevance
“…Treating CODs requires a thorough assessment of the patient's needs, a practical knowledge of one's own treatment resources and those of the local community, and the ability to establish a relationship with the patient that encourages him or her to become an active participant in the recovery process. A recent review concluded that there is no established integrated method of treating CODs in adults that is clearly efficacious and replicable [30]. Even so, the same review found that many interventions for SUDs were efficacious in the COD population, and many interventions for MHDs were also effective in COD.…”
Section: Treatmentmentioning
confidence: 95%
“…Treating CODs requires a thorough assessment of the patient's needs, a practical knowledge of one's own treatment resources and those of the local community, and the ability to establish a relationship with the patient that encourages him or her to become an active participant in the recovery process. A recent review concluded that there is no established integrated method of treating CODs in adults that is clearly efficacious and replicable [30]. Even so, the same review found that many interventions for SUDs were efficacious in the COD population, and many interventions for MHDs were also effective in COD.…”
Section: Treatmentmentioning
confidence: 95%
“…1 b 5 0 0 2 n i s a H -C R A S E N e s u b A 4 drugs before abuse and dependence develop (Kendler et al, 2011;Kushner et al, 2012). There are numerous guidelines and reviews summarising the management and treatment of patients with a dual diagnosis which include psychosocial or integrated share-care approaches or treatment in parallel systems (Drake et al, 2008;Horsfall et al, 2009;Mills et al, 2009;Tiet and Mausbach, 2007). Comorbidity in patients with serious mental illness is difficult to treat as there are many service barriers that need to be overcome (McGovern et al, 2006;Mills et al, 2012).…”
Section: Understanding and Treating Comorbiditymentioning
confidence: 97%
“…Initial studies of brief physician advice have shown promise in older adults (Fleming, Manwell, Barry, Adams, & Stauffacher, 1999). Tiet and Mausbach (2007) reviewed this literature and found that existing efficacious treatments for reducing psychiatric symptoms also tend to be effective in patients with co-occurring disorders and that existing efficacious treatments for reducing substance use also decrease substance use in patients with dual diagnoses. Norton (1998) recommended that interventions be tailored toward the older individual and delivered in treatment groups with similarly aged cohorts to increase comfort and adherence.…”
Section: Treatmentmentioning
confidence: 97%